Confirmatory Tests for the Diagnosis of Primary Aldosteronism: A Prospective Diagnostic Accuracy Study. Issue 1 (January 2018) - Song, Ying; Yang, Shumin; He, Wenwen; Hu, Jinbo; Cheng, Qingfeng; Wang, Yue; Luo, Ting; Ma, Linqiang; Zhen, Qianna; Zhang, Suhua; Mei, Mei; Wang, Zhihong; et al.
Abstract : The diagnosis of primary aldosteronism typically requires at least one confirmatory test. The fludrocortisone suppression test is generally accepted as a reliable confirmatory test, but it is cumbersome. Evidence from accuracy studies of the saline infusion test (SIT) and the captopril challenge test (CCT) has provided conflicting results. This prospective study aimed to evaluate the diagnostic accuracy of the SIT and CCT using fludrocortisone suppression test as the reference standard. One hundred thirty-five patients diagnosed with primary aldosteronism and 101 patients diagnosed with essential hypertension who completed the 3 confirmatory tests were included for the diagnostic accuracy analysis. The areas under the receiver–operator characteristics curves of the CCT and SIT were 0.96 (95% confidence interval [CI], 0.92–0.98) and 0.96 (95% CI, 0.92–0.98), respectively, using post-test plasma aldosterone concentration (PAC) for diagnosis. However, the areas under the receiver–operator characteristics curves of the CCT decreased to 0.71 (95% CI, 0.65–0.77) when the PAC suppression percentage was used to diagnose primary aldosteronism. The optimal cutoff of PAC post-CCT was set at 11 ng/dL, resulting in a sensitivity of 0.90 (95% CI, 0.84–0.95) and a specificity of 0.90 (95% CI, 0.83–0.95), which were not significantly different from those of SIT (with PAC post-SIT set at 8 ng/dL, sensitivity: 0.85 [95% CI, 0.78–0.91], P =0.192; specificity: 0.92 [95% CI, 0.85–0.97], P =0.551). In conclusion, both CCT and SIT are accurate alternatives to the more complex fludrocortisone suppression test. Because CCT is safe and much easier to perform, it may serve as a more feasible alternative. When interpreting the results of CCT, PAC post-CCT is highly recommended. Abstract : Supplemental Digital Content is available in the text.